Presenteeism when employers are under pressure: evidence from a high-stakes environment - Mario Lackner; Hendrik Sonnabend (Economica, 2023)
This study analyses whether the decision to work while sick can be linked to workload fluctuations. Drawing on data collected from professional football, we exploit the dynamics of a season and use additional (national and international) cup games conducted in the second half of a season as a source of exogenous variation. We find robust evidence that players are 6.3~percentage points more likely to return from injuries earlier than expected when their teams are exposed to a high workload. The effect is driven by players who are more important to their teams and those who are less vulnerable to injuries. Finally, we find that presenteeism comes at the cost of an early comeback significantly shortening the time until the next injury by approximately 16~days.
Keywords: 330